A Green and Efficient Method for the Preconcentration and Determination of Gallic Acid, Bergenin, Quercitrin, and Embelin from Ardisia japonica Using Nononic Surfactant Genapol X-080 as the Extraction Solvent. (1st February 2018) - Chen, Ying; Du, Kunze; Li, Jin; Bai, Yun; An, Mingrui; Tan, Zhijing; Chang, Yan-xu
Abstract : A simple cloud point preconcentration method was developed and validated for the determination of gallic acid, bergenin, quercitrin, and embelin in Ardisia japonica by high-performance liquid chromatography (HPLC) using ultrasonic assisted micellar extraction. Nonionic surfactant Genapol X-080 was selected as the extraction solvent. The effects of various experimental conditions such as the type and concentration of surfactant and salt, temperature, and solution pH on the extraction of these components were studied to optimize the conditions of Ardisia japonica . The solution was incubated in a thermostatic water bath at 60°C for 10 min, and 35% NaH2 PO4 (w/v) was added to the solution to promote the phase separation and increase the preconcentration factor. The intraday and interday precision (RSD) were both below 5.0% and the limits of detection (LOD) for the analytes were between 10 and 20 ng·mL −1 . The proposed method provides a simple, efficient, and organic solvent-free method to analyze gallic acid, bergenin, quercitrin, and embelin for the quality control of Ardisia japonica .